O5E.2 A hospital occupational diseases unit: an experience to increase the recognition of occupational disease. (April 2019) - Benavides, FG; Ramada, JM; Ubalde-Lopez, M; Delclos, GL; Serra, C
Abstract : Background: Under-reporting and recognition of occupational diseases is a problem in countries with workers' compensation schemes. Aims: To describe the role of a public hospital Occupational Disease Unit (ODU) in Barcelona that resulted in improved reporting and official recognition of occupational diseases from 2010 to 2017. Methods: Hospital physicians referred possible cases of work-related disease to the ODU, where in-depth medical evaluations were then performed, and a detailed report addressing causation was generated. Patients with confirmed cases of occupational disease were counselled and followed while pursuing official recognition and benefits claims by the Spanish Social Security System. Results: Between 2010 and 2017, 149 cases were referred to the ODU for evaluation. Of these, 80 (53.7%) were confirmed to have an occupational disease, 54 (67.5%) patients pursued official recognition, and to date 26 (48.1%) were accepted by the Social Security System. The predictive positive value varied by diagnosis group (p=0.003), and was highest for skin diseases (71.4%) and cancer (66.7%), and lowest for hearing loss (29.4%) and musculoskeletal disorders (16.7%). Conclusions: A hospital ODU can improve reporting and official recognition of occupational diseases, that otherwise might not have been recognized. Expanding this experience to other Spanish and European hospitals could improve the efficiency of workers' compensation schemes and better support preventive policies.